2018
DOI: 10.1111/myc.12798
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal mucormycosis in apparently immunocompetent hosts—A review

Abstract: The diagnosis of gastrointestinal (GI) mucormycosis is always a challenge due to its non-specific clinical presentations and often diagnosed at autopsy. Recently increased number of GI mucormycosis has been reported in immunocompetent hosts and during 1948 through 2017, 200 cases of GI mucormycosis are available in literature. We could review 176 cases where case details were available. Majority (50.6%) of the cases were reported from Asia. The disease is nearly equally recorded in adults and paediatric popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 120 publications
2
66
0
2
Order By: Relevance
“…Even after surgical treatment and antifungal treatment mortality remains high (60-70%). 5 In the past many antifungals have been tried but mucorales are resistant to each one. Only Amphotericin B is active against the mucorales.…”
Section: Discussionmentioning
confidence: 99%
“…Even after surgical treatment and antifungal treatment mortality remains high (60-70%). 5 In the past many antifungals have been tried but mucorales are resistant to each one. Only Amphotericin B is active against the mucorales.…”
Section: Discussionmentioning
confidence: 99%
“…1 Mucormycosis of the gastrointestinal tract is rare and possibly accounts for around 8% of all cases of mucormycosis and is associated with a mortality of around 50%. 2 It is difficult to diagnose. In particular, gastrointestinal mucormycosis has been seen in premature neonates, often in association with widespread disseminated disease.…”
Section: Discussionmentioning
confidence: 99%
“…Rare cases of gastrointestinal mucormycosis have been described in association with other immune-compromising conditions, including AIDS, systemic lupus erythematosus, and organ transplantation. 2 In a recent systematic review on gastrointestinal mucormycosis, most of the reported cases were from Asia. Although gastric mucormycosis may be easy to diagnose, a recent review suggests that the stomach is the commonest organ involved in adults, whereas intestinal involvement is more frequent in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations